FMCW Monopulse Radar with an Orthogonally Polarized Dual-Beam Dielectric Resonator Antenna - Lee, Chanhee; Shin, Kyeong Han; Lee, Ji Hoon; Lee, Hyo Won; Kim, Jeong Wook; Yu, Jong Won (ISAP 2024 - International Symposium on Antennas and Propagation, 2024)
In this paper, frequency-modulated continuous-wave (FMCW) radar system using dielectric resonator antenna (DRA), which has two beams with orthogonal linear polarization to each other, is introduced to function as a monopulse radar. The DRA operates at 24.3 GHz with a 16.8% bandwidth and provides over 40 dB isolation between V-pol and H-pol ports. Simulations demonstrate effective target detection and advanced directional information extraction, similar to monopulse radar, using a signal processing technique to address overlapping beam regions.
Keywords: Dielectric-resonator antennas; Dual-beam; Frequency modulated continous waves; Frequency-modulated continuous-wave monopulse radar; Frequency-modulated-continuous-wave radars; Linear polarization; Monopulse; Orthogonal polarizations; Simulation demonstrate; Two beams; dielectric resonator antenna; dual-beam; FMCW monopulse radar; orthogonal polarization